Implementasi E-Modul Pembelajaran untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Dasar-Dasar Ketenagalistrikan - Ning Tias, Tiara; Asnil, Asnil (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This study was conducted to analyze the Implementation of learning e-modules to improve the learning outcomes of vocational high school students in basic electrical engineering. The method used is quantitative analysis. This study uses an experimental method in the form of a true experiment design. This study uses pretest and posttest research instruments in objective form to see the learning outcomes of students. It is tested using validity tests, reliability tests, discrimination power tests, and question difficulty index to determine the feasibility of the instruments used. The pretest and posttest results were analyzed using the completeness of learning outcomes and effect size calculations. The study's results indicate that the application of e-modules to basic electrical engineering can improve student learning outcomes. These results can be seen from the results of the pretest and posttest which were analyzed using the completeness of learning outcomes showing that many students achieved the minimum completeness criteria set by the school and the effect size analysis which had a large influence by using e-modules in improving student learning outcomes.